MitoSeg: Mitochondria segmentation tool - Faris Serdar Taşel; Efe Çi̇ftci̇ (SoftwareX)
Recent studies suggest a potential link between the physical structure of mitochondria and neurodegenerative diseases. With advances in Electron Microscopy techniques, it has become possible to visualize the boundary and cristae structures of mitochondria in detail. Segmenting mitochondria from microscopy images remains challenging due to image quality and complex morphology of mitochondria, including cristae and the other subcellular structures. It is crucial to automatically segment mitochondria from images exhibiting different mitochondrial boundary and crista characteristics to investigate the relationship between mitochondria and diseases. In this paper, we present a software solution for mitochondrial segmentation using an automatic validation scheme based on the general physical properties of mitochondria, highlighting boundaries in electron microscopy tomography images and generating corresponding 3D meshes. These capabilities help researchers conduct further investigations into mitochondrial morphology and explore its role in the mechanisms of neurodegenerative diseases.